Hip Arthroscopy Outcomes in NFL and Collegiate American Football Players: Single Surgeon Experience with Return to Play, Sustained Return to Play, and Attrition Analysis. Issue 7 (30th July 2021) - McGaver, Rebecca; Seiffert, Kayla; Giveans, Russell; Larson, Christopher
Objectives: There has been substantial literature regarding return to play after hip arthroscopy for professional athletes. There is less data with regards to both NFL and Collegiate football players and differences in outcomes between these athletic populations. Our hypothesis was that an arthroscopic FAI corrective procedure in NFL and Collegiate football players would result in improved PROM's, predictable return to play rates, with higher return to play rates in NFL players vs Collegiate players. Methods: Between 2011 – 2019, 76 hips (65 players) in NFL and Collegiate American football players underwent hip arthroscopy and FAI correction by a single surgeon. An arthroscopic FAI correction procedure was performed for all athletes as previously described by the senior author. All athletes were prospectively followed preoperatively and postoperatively with HOS ADL, HOS Sports, modified Harris Hip, SF-12, VR-12 Physical, VR-12 Mental, and VAS patient related outcomes measures (PROMs). Plain radiographs were evaluated preoperatively and postoperatively with regards to Pincer-type FAI (LCE angle, Cross-over sign (COS), Cam-type FAI (alpha angle on AP and 45 degree modified Dunn radiographs), and Tonnis arthritis grade. Return to play on the roster, return to a game, number of seasons played, and number of games played were retrospectively evaluated via internet search of their respective teams, discussions with team ATC's, Team Physicians, and Players themselves. Reasons for not returning or no longer playing were also searched and inquired. Players were followed until retirement from the NFL, graduation from collegiate football, or until they no longer were able to play because of injury, by choice, or were cut / released by the club. Results: There were 12 hips in NFL football players and 64 hips in Collegiate American football players. Of the Collegiate players, 31 hips played Division 1, 16 hips played Division 2, and 18 hips played Division 3 level football. The most common positions in this cohort were Linemen (27.7%) and Defensive backs (33.8%). The mean follow-up for all players was 33.4 months. There was a significant improvement for all players for PROMs (Pre to Post, mHHS 70.3 to 95, HOS Sports 52.6 to 92.8, HOS ADL 74.8 to 98.4, SF-12 83.2 to 91.4, VAS 5.2 to 0.9) at mean latest F/U (p<0.01 for each). The rate of return to football for all players was 77.6%. The rate of Return for NFL players was 90%, as compared to 75% for collegiate players (72% D1, 83% D2, 73% D3) (p=.062). The mean number of seasons played after arthroscopy was 2.1 for NFL players (range, 1-5) and 1.74 (range, 1-3) for collegiate athletes. The mean number of games played after arthroscopy was 34.7 games (range, 17-100) for NFL and 17.1 games (range, 0-33) for collegiate players. Six of 12 (50%) NFL players remain active in the NFL and of the 5 not active, 1 was drafted in the 4 th round, and 4 were undrafted free agents. All 4 NFL players drafted in the first round remain active in the NFL although one is currently a free agent. An additional 4 collegiate players (5 hips, All D1 athletes) went on to play in the NFL. Only 9.2% (6 players, 7 hips) of players cited continued hip pain as a reason for attrition and all were collegiate players. No NFL players cited persistent hip issues as a reason for attrition. Other reasons for attrition included graduation from college (4 hips, 5.3%), other non-hip related injuries (1 hip, 1.3%), being cut or waived by the club (4 hips, 5.3%), and choosing not return to football (non-injury related) (6 hips, 7.9%). Conclusions: Hip arthroscopy led to a predictable improvement in patient related outcomes measures at a mean 33 months follow-up for NFL and collegiate American football players. NFL players were more likely to return to play than collegiate athletes (90% vs 75%, although non-significant with the numbers available), and higher round draft picks had greater sustained return to play compared to lower round / undrafted free agents. Attrition was rarely the result of persistent hip related pain and was multifactorial in nature in particular for collegiate athletes.